Sequence and partial functional analysis of canine Bcl-2 family proteins. (February 2016) - de Brot, S.; Schade, B.; Croci, M.; Dettwiler, M.; Guscetti, F.
Abstract: Dogs present with spontaneous neoplasms biologically similar to human cancers. Apoptotic pathways are deregulated during cancer genesis and progression and are important for therapy. We have assessed the degree of conservation of a set of canine Bcl-2 family members with the human and murine orthologs. To this end, seven complete canine open reading frames were cloned in this family, four of which are novel for the dog, their sequences were analyzed, and their functional interactions were studied in yeasts. We found a high degree of overall and domain sequence homology between canine and human proteins. It was slightly higher than between murine and human proteins. Functional interactions between canine pro-apoptotic Bax and Bak and anti-apoptotic Bcl-xL, Bcl-w, and Mcl-1 were recapitulated in yeasts. Our data provide support for the notion that systems based on canine-derived proteins might faithfully reproduce Bcl-2 family member interactions known from other species and establish the yeast as a useful tool for functional studies with canine proteins. Highlights: We have cloned selected canine Bcl-2 family members and analyzed their sequences. Canine Bcl-2 proteins display a high degree of homology with their human counterparts. We have successfully established a yeast model for functional studies of canine Bcl-2 proteins.